Pengelolaan Pembelajaran yang Efektif di Sekolah Dasar dalam Menyusun Rencana Pembelajaran yang Menarik - Adha Zam Zam Hariro; Atikah Zahrani; Fenika Ardiyani; Safran Hasibuan (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This study aims to identify effective learning management in elementary schools in preparing interesting learning plans. Teachers really determine the success of students, especially in relation to the teaching and learning process, and are the component that has the most influence on the creation of quality educational processes and results so that teachers are required to have competence or ability, quality and professionalism. This research uses a qualitative descriptive method where in-depth interviews and observations are carried out on the research subjects. The research results show that effective learning management in elementary schools requires a learning implementation planning strategy. A teacher is required to have a learning implementation plan in order to create an interesting and enjoyable learning atmosphere which of course will also create effective learning. This study also identified factors that make the learning process ineffective, one of which is the way a teacher teaches. By preparing a learning implementation plan, effective learning management in elementary schools can be realized. This research also has implications in the broader context of primary school education in Indonesia.